2014
DOI: 10.1002/jcb.24893
|View full text |Cite
|
Sign up to set email alerts
|

The SAP Motif and C‐Terminal RS‐ and RD/E‐Rich Region Influences the Sub‐Nuclear Localization of Acinus Isoforms

Abstract: Acinus has been reported to function in apoptosis, RNA processing and regulation of gene transcription including RA-dependent transcription. There are three different isoforms of Acinus termed Acinus-L, Acinus-S′ and Acinus-S. The isoforms of Acinus differ in their N-terminus while the C-terminus is consistent in all isoforms. The sub-nuclear localization of Acinus-L and Acinus-S′ was determined using fluorescence microscopy. Acinus-S′ colocalizes with SC35 in nuclear speckles while Acinus-L localizes diffusel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…RNPS1 is also a component of two alternative complexes [ 29 ], ASAP (Acinus, RNPS1 and SAP18) and PSAP (Pinin, RNPS1 and SAP18). Although both complexes are involved in splicing regulation, the outcomes (whether a splicing event is promoted or inhibited) can be quite different dependent on what other protein factors they interact with [ 30 ]. With the revealed protein network in mind, it is of importance to investigate the identity, fate and function of immediate transcript targets of SR45 and SR45-associated protein networks in order to understand how SR45 regulates splicing in supporting the success of a biological system.…”
Section: Discussionmentioning
confidence: 99%
“…RNPS1 is also a component of two alternative complexes [ 29 ], ASAP (Acinus, RNPS1 and SAP18) and PSAP (Pinin, RNPS1 and SAP18). Although both complexes are involved in splicing regulation, the outcomes (whether a splicing event is promoted or inhibited) can be quite different dependent on what other protein factors they interact with [ 30 ]. With the revealed protein network in mind, it is of importance to investigate the identity, fate and function of immediate transcript targets of SR45 and SR45-associated protein networks in order to understand how SR45 regulates splicing in supporting the success of a biological system.…”
Section: Discussionmentioning
confidence: 99%
“…Acinus through its C‐terminal region interacts with RNPS1 and SAP18 to form the ASAP complex, which is part of the EJC (Schwerk et al, ; Tange et al, ). In addition, the sub‐nuclear localization of RNPS1 is affected by Acinus (Wang et al, ). RNPS1 is a SR‐related protein and functions in regulating constitutive and alternative splicing.…”
Section: Resultsmentioning
confidence: 99%
“…However, Acinus was shown to have little activity in regulating pre‐mRNA splicing (Schwerk et al, ; Singh et al, ), which raises the question about the function of Acinus found in spliceosomes and the EJC. In addition, whether Acinus‐L and Acinus‐S’ have distinct functions in regulating pre‐mRNA splicing due to their distinct sub‐nuclear localizations (Wang et al, ) is unclear. Previous studies from our laboratory have identified Acinus‐S’ as a corepressor of RAR‐dependent gene expression (Vucetic et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Acin1-L, Acin1-S , and Acin1-S' transcripts are transcribed from the Acin1 gene through alternative promoter usage or an AS mechanism [46] . All Acin1 isoforms share an RNA recognition motif, RSB domain, and RS-rich region within its C-terminus, whereas the N-terminal SAP motif within Acin1-L mediates its interaction with AT-rich DNA regions [47 , 48] . Proteomic assays indicated the nuclear distribution of the Acin1-S and Acin1-S ' isoforms, whereas the nuclear-cytoplasmic localization of the Acin1-L isoform was relevant to its SAP motif [47] .…”
Section: Discussionmentioning
confidence: 99%
“…All Acin1 isoforms share an RNA recognition motif, RSB domain, and RS-rich region within its C-terminus, whereas the N-terminal SAP motif within Acin1-L mediates its interaction with AT-rich DNA regions [47 , 48] . Proteomic assays indicated the nuclear distribution of the Acin1-S and Acin1-S ' isoforms, whereas the nuclear-cytoplasmic localization of the Acin1-L isoform was relevant to its SAP motif [47] . Even though Acin1 was first characterized as an RNA-binding protein involved in apoptosis, the influences of respective Acin1 isoforms on apoptotic signatures are uncharacterized [33] .…”
Section: Discussionmentioning
confidence: 99%